2019
DOI: 10.1099/jgv.0.001327
|View full text |Cite
|
Sign up to set email alerts
|

A novel murine model of differentiation-mediated cytomegalovirus reactivation from latently infected bone marrow haematopoietic cells

Abstract: CD34+ myeloid lineage progenitor cells are an important reservoir of latent human cytomegalovirus (HCMV), and differentiation to macrophages or dendritic cells (DCs) is known to cause reactivation of latent virus. Due to its species-specificity, murine models have been used to study mouse CMV (MCMV) latency and reactivation in vivo. While previous studies have shown that MCMV genomic DNA can be detected in the bone marrow (BM) of latently infected mice, the identity of these cells has not been defined. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…While it is understood that our work did not address each and every organ and cellular site in the body, we targeted our efforts towards the organs that were frequently considered in the study of virus latency. We identified viral genomes in macrophages and endothelial cells, in line with previous reports (6, 7, 11, 24), but we also identified the stromal cells as a major contributor to the pool of latent genomes. It is notable that viral genomes in fibroblastic cells were transcriptionally muted and expressed only few transcripts, predominantly immediate-early ones, in line with previous reports (22, 27, 28).…”
Section: Discussionsupporting
confidence: 89%
“…While it is understood that our work did not address each and every organ and cellular site in the body, we targeted our efforts towards the organs that were frequently considered in the study of virus latency. We identified viral genomes in macrophages and endothelial cells, in line with previous reports (6, 7, 11, 24), but we also identified the stromal cells as a major contributor to the pool of latent genomes. It is notable that viral genomes in fibroblastic cells were transcriptionally muted and expressed only few transcripts, predominantly immediate-early ones, in line with previous reports (22, 27, 28).…”
Section: Discussionsupporting
confidence: 89%
“…Entry was significantly reduced for all R131 and R129 mutants in dendritic cells, macrophages, and bone marrow cells, which is consistent with pentamer mutants in other CMV species ( Table 3 ). Previous studies identified CD34+ progenitor cells in bone marrow as a site of CMV latency [ 109 , 110 ]. Further work is necessary to determine if pentamer mutants show impaired abilities to establish latency.…”
Section: Discussionmentioning
confidence: 99%
“…Stress or differentiation pathways are typically associated with reactivation from latency [ 24 , 29 , 36 , 50 , 109 ]. But how does the virus “sense” and “respond” to changes in the infected cell to navigate the “decisions” to sustain the latent program or to reactivate?…”
Section: Mechanisms Of Ul133-ul138 Function Andmentioning
confidence: 99%